2008
DOI: 10.3133/sir20085099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Observed and Predicted Abutment Scour at Selected Bridges in Maine

Abstract: Vertical coordinate information is referenced to the North American Vertical Datum of 1988 (NAVD 88). Horizontal coordinate information is referenced to the North American Datum of 1983 (NAD 83).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Dey and Barbhuiya (2004b) suggested that K ó can be determined using a graph of K ó versus ó g : It can be seen that the presented K ó is in agreement with the results obtained by Dey and Barbhuiya (2004b). Table 5 shows the error measures of PR2 and the previous formulas for field data collected by Lombard and Hodgkins (2008). The l/y values in this dataset vary from 0 to 244 .…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Dey and Barbhuiya (2004b) suggested that K ó can be determined using a graph of K ó versus ó g : It can be seen that the presented K ó is in agreement with the results obtained by Dey and Barbhuiya (2004b). Table 5 shows the error measures of PR2 and the previous formulas for field data collected by Lombard and Hodgkins (2008). The l/y values in this dataset vary from 0 to 244 .…”
supporting
confidence: 86%
“…In addition, the range of ó g shows that most of the experiments were conducted using uniform sediments and the d 50 ranges indicate that both fine and coarse sediments were studies. In addition, 100 field measurements collected by Lombard and Hodgkins (2008) from different bridges were used in this study.…”
Section: Description Of Datasetsmentioning
confidence: 99%
“…All the field data compiled from the literature review were collected by the USGS. The field data included 15 measurements from the USGS National Bridge Scour Database (NBSD) (3,9); 92 from moderate-gradient streams of the South Carolina Piedmont with cohesive sediments (8); 106 from low-gradient streams of the South Carolina Coastal Plain (none are tidally influenced), generally with sandy, noncohesive sediments (8); 93 from small, steep-gradient streams in Maine with coarse sediments (5); and 23 from low-gradient streams in the Alabama Black Prairie Belt, with cohesive sediments (10). [The Alabama data were originally classified as contraction scour (10).…”
Section: Field Datamentioning
confidence: 99%
“…The complexity of abutment scour processes has made it difficult to formulate prediction methods, and few would dispute the above assessment by Ettema et al (1). Current scour prediction equations largely consist of semiempirical relations developed from simplified laboratory investigations (2), and the performance of these equations can vary (3)(4)(5). While overprediction occurs frequently (and at times excessively), underprediction also is of concern.…”
mentioning
confidence: 99%
“…These data were collected in part to form a database to evaluate the performance of scour-prediction equations and to understand abutment-scour trends in the field setting. Currently available USGS abutment-scour data include 208 measurements in South Carolina (Benedict, 2003) Wagner and others, 2006), and 100 measurements in Maine (Lombard and Hodgkins, 2008). The South Carolina database was the primary source for developing the original (Benedict, 2003) clear-water abutment-scour envelope curves and also served as the primary data source for developing the modified envelope curves in this investigation.…”
Section: Selected Field Data Used In the Analysismentioning
confidence: 99%